Appropriateness of Omeprazole Prescribing in Quebec’s Senior Population - Jean-Pierre Grégoire; Jocelyne Moisan; Isabelle Chabot; Michel Gaudet (Canadian Journal of Gastroenterology)
BACKGROUND: Prescribing omeprazole for the treatment of digestive disorders accounts for an important part of the costs in Quebec’s drug benefit plan. In July 1993, the Quebec drug program listed omeprazole, with restriction, in its formulary. On January 1, 1994, this restriction was lifted; since then, omeprazole has been listed in the regular provincial formulary.